Refiguring prose style : possibilities for writing pedagogy - Johnson, T. R., 1964-; Pace, Tom, 1969- (Utah State University Press, 2005)
This collection takes up a comprehensive study of stylistics in the teaching of writing in higher education. Part I explores the recent history of composition studies, the ways it has figured and all but effaced the whole question of prose style. Part II takes to heart Elbow's suggestion that composition and literature, particularly as conceptualized in the context of creative writing courses, have something to learn from each other. Part III sketches practical classroom procedures for heightening students' abilities to engage style, and part IV explores new theoretical frameworks for defining.